Preparation procedure to obtain iron nanopowder under non-isothermal conditions - Nguyen, Tien Hiep; Nguyen, Van Minh; Nguyen, Manh Hung; Danchuk, Vitaly N. (Journal of the Belarusian State University. Chemistry, 2021)
The kinetics for the procedure of preparing iron nanopowder from α-FeOOH by hydrogen reduction under non-isothermal conditions were studied. The reduction of α-FeOOH nanopowder was shown to occur within the temperature range from 180 to 550 °С, with a maximum specific rate value attained at 500 °С. The activation energy for the reduction process α-FeOOH nanopowder was measured to be 43 kJ/mol, evidencing a mixed reaction mode. Performing the reduction of α-FeOOH at 500 °С accelerated the process while ensuring the required properties of the product obtained. The Fe nanoparticles thus prepared were of rounded shape, the size ranging from 70 to 100 nm.